If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -1)(x + -1) = 0 Reorder the terms: (-1 + 5x)(x + -1) = 0 Reorder the terms: (-1 + 5x)(-1 + x) = 0 Multiply (-1 + 5x) * (-1 + x) (-1(-1 + x) + 5x * (-1 + x)) = 0 ((-1 * -1 + x * -1) + 5x * (-1 + x)) = 0 ((1 + -1x) + 5x * (-1 + x)) = 0 (1 + -1x + (-1 * 5x + x * 5x)) = 0 (1 + -1x + (-5x + 5x2)) = 0 Combine like terms: -1x + -5x = -6x (1 + -6x + 5x2) = 0 Solving 1 + -6x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -5x)(1 + -1x) = 0Subproblem 1
Set the factor '(1 + -5x)' equal to zero and attempt to solve: Simplifying 1 + -5x = 0 Solving 1 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5x = 0 + -1 -5x = 0 + -1 Combine like terms: 0 + -1 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {0.2, 1}
| 2x-97=x+4 | | -8+2x=4x-6 | | 2x-95=x+4 | | 6x+8-x=-47 | | 3=5(x-4)+1-4x | | -4x-x=11(4x-11)+4(4-11x) | | 3=5(x-4)*1-4x | | 6m+3n+4m+8n= | | y=x^2-6x+k | | f(x+4)=x^2+2x-8 | | 5-3y+y= | | 65-13.5(0.2P-1.5)=7.5 | | 0.05P+0.07(1200-P)=80 | | 11(1-9x)=-7-12(5x-8) | | -5x+4y= | | 3/6-2/15 | | 152.34=2.95h+72.69 | | 4(3x+1)=5x-8x | | 7x^3e^7x-3x^2e^7x/x^6 | | 11(1+2p)+8(1-7p)=-7p-8p | | (6x^4)-(24x^2)=0 | | x/2=x/3=-10 | | x-1=-3+x | | -2-3n=-2(1+4n) | | q-10whenq=13 | | 2y^2-y=28 | | 10y=2x-15 | | 161/14 | | -8a-5=163 | | 14/161 | | x2-2=-7x/4 | | tan(2x)=tan(x+30) |